Pulitzer's Post-dispatch, 1878-1883 - Rammelkamp, Julian S. (Princeton legacy library., 1967)
Professor Rammelkamp examines the St. Louis Post-Dispatch during its formative years, seeing it as the foundation of the highly successful World and of Pulitzer's career itself.Originally published in 1967.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.